Establishing Criteria for Zakat Collectors in the Management of Zakat Fitrah Funds - Zami, Muhammad Taufiq Zam; Heni Satar Nurhaida (International Journal of Social Science and Religion (IJSSR), 2025)
This study examines the operational criteria for selecting and evaluating amil zakat in managing zakat fitrah funds in Salatiga City, Indonesia. It aims to identify challenges and propose reforms to enhance accountability and equitable distribution of zakat, supporting poverty alleviation. This research uses a qualitative field research design, data were collected via semi-structured interviews, observations, and document review in several mosques and UPZ units in Salatiga City. Content analysis identified key themes and examined selection criteria and administrative challenges with rigorous precision. The findings reveal that informal appointment practices and lack of standardized competency assessments undermine effective zakat management. Inconsistent distribution practices, seasonal collections, and reliance on ad hoc committees’ compromise transparency, reducing the socio-economic impact of zakat fitrah funds across community levels. The study’s results offer actionable recommendations for policymakers and zakat institutions. They are useful for enhancing governance in Islamic social finance, guiding reforms in zakat management, and improving equitable resource allocation in community development, religious studies, and socio-economic policy globally. The novelty, uniquely integrates traditional Islamic jurisprudence with modern administrative practices to develop a replicable framework for amil zakat selection. It advances current knowledge by addressing a critical gap in operational mechanisms, offering innovative insights into enhancing zakat management efficacy.